An indigenous oral history reader - Schwartz, Bryan P.; Schwartz, Bryan P.; Brand, Shira; Gobin, Janelle; Edkins, Tamara (Bryan P. Schwartz, 2022)
"The oral history of Indigenous people in Canada has been recognized by mainstream legal systems in Canada over the past few decades as being of fundamental importance in court cases and negotiations with Indigenous peoples. As Indigenous peoples further exercise their right to self-government, they will continue drawing their oral traditions to define and develop their autonomous legal system. This anthology attempts to collect a wide variety of materials that embody many perspectives. It attempts to place those materials within a conceptual framework that might be helpful in looking at Indigenous oral history, and indeed oral history generally. That framework includes viewing oral history in three dimensions of time - testimony about recent events, oral histories that encompass an individual's lifetime, and oral traditions that are passed down from generation to generation. The framework includes looking at oral history in the context of how many cultures and traditions incorporate oral history in their legal systems and cultures. It asks both how values and methods differ among communities and how they reflect widespread or virtually universal tendencies. The framework also invites the reader to consider the different ways in which oral evidence can or should be reinforced or qualified by references to other sources of information, such as other oral evidence, documentary testimony and physical evidence of various kinds. It is hoped that this collection will be of assistance to others in studying or developing their own teaching materials in this dynamic area."--Back cover.